Are the religious suspicious of science? Investigating religiosity, religious context, and orientations towards science. (November 2018) - Chan, Esther
Are the religious suspicious of science? Drawing on data from 52 nations in the World Values Survey (wave 6) ( N  = 58, 474), I utilize multilevel models to examine the relationship between religiosity, religious context, and five different orientations towards science: confidence in science, trust in scientific authority under conditions of conflict with religion, faith in science, views on the moral effects of science, and interest in scientific knowledge. Results show that while religiosity is on average negatively associated with the five outcomes, the relationship between religiosity and orientations towards science varies by country such that religiosity is sometimes positively associated with the different outcomes. Religiosity is only consistently negatively associated with trust in scientific authority in all countries and with all orientations towards science in western countries. Finally, differences in orientations towards science also exist across country religious contexts, with countries dominated by the unaffiliated having more positive orientations towards science.